EFFICACY AND SAFETY OF APREMILAST IN MODERATE TO SEVERE CASES OF CHRONIC PLAQUE PSORIASIS: A RETROSPECTIVE STUDY - KHAN, S; FAROOQ, M; TARIQ, F; AHMED, R; ASLAM, MA (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study was to assess the efficacy and safety of Apremilast in patients with moderate-to-severe plaque psoriasis. A retrospective study was conducted in the Dermatology Department of Bakhtawar Amin Trust Hospital Multan from September 2021 to September 2022. A total of 102 patients were included in the study after evaluation. Apremilast was administered in all the patients, and its clinical response was assessed by the extent of Psoriasis Area Severity Index (PASI) reduction 16 weeks after the start of treatment. Our secondary endpoints included examining the PASI; Dermatology Life Quality Index (DLQI); Physician Global Assessment (PGA); the adverse effects of treatment; survival rate; reasons for discontinuation of treatment, if any, and the rate of patients who managed to reach Psoriasis Area Severity Index reduction up to 50%, 75%, 90% and 100% after 16 weeks. 37 (72.5%) subjects achieved PASI reduction ≥75% or ≥50%, thus achieving the primary endpoint. The majority of the study sample had moderate psoriasis, with a mean baseline DLQI score of 11.2, PASI score of 11.0 and PGA score 2.6. After 16 weeks, 65% subjects had PGA score ≤1. PASI improved rapidly over 4 (4.8) (P<.001) to 16 weeks (4.3) (P<.001). DLQI at baseline was 11.2; after 16 weeks, it was 3.8 (P<.001). Regarding secondary endpoints, after 16 weeks, 35/37 (94.5%) subjects achieved ΔPASI≥50, 18/37 (48.6%) ΔPASI≥75, 8/37 (21.6%) achieved ΔPASI≥90 and 6/37(16.2%) achieved ΔPASI100. Treatment-related adverse effects occurred in 16/51 (31.3%) patients. In total, treatment was stopped in 6 (11.6%)subjects because of adverse effects; gastrointestinal disorders were the most common. Apremilast is an effective and safe drug for the treatment of patients with moderate-to-severe plaque psoriasis.